User Tools

Site Tools


math121a-f23:october_6_friday

Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Next revision
Previous revision
math121a-f23:october_6_friday [2023/10/05 21:14]
pzhou created
math121a-f23:october_6_friday [2023/10/05 22:45] (current)
pzhou [October 6 (Friday)]
Line 1: Line 1:
 ====== October 6 (Friday) ====== ====== October 6 (Friday) ======
 +
 +Topics: 
 +  * Fourier inversion formula
 +  * Fourier Series for periodic function 
 +  * Interpretation of complex vector space, hermitian inner product, orthonormal basis. 
 +
 +===== Inversion Formula =====
 +Suppose you started from f(x)f(x), and did some hard work to get the Fourier transformation F(p)F(p). Can you recover f(x)f(x) from F(p)F(p)? Did you lose information when you throw away f(x)f(x) and only keep F(p)F(p)
 +
 +If f(x)f(x) is continuous and absolutely integrable, we can recover f(x)f(x) from F(p)F(p) by 
 +f(x)=12πpRF(p)eipxdp f(x) = \frac{1}{2\pi} \int_{p \in \R} F(p) e^{ipx} dp
 +The proof of this theorem is beyond the scope of this class. You might be happy to just accept the formal 'rule' that
 +12πReipxipydp=δ(xy). \frac{1}{2\pi} \int_\R e^{ipx - ipy} dp = \delta(x-y).
 +and that
 +f(x)=δ(xy)f(y)dy f(x) = \int \delta(x-y) f(y) dy
 +
 +We can try some example to see if it works. 
 +
 +===== Fourer Series =====
 +If the function f(x)f(x) is a periodic function, of period LL, meaning f(x)=f(x+L)f(x) = f(x+L), then we cannot do Fourier transform (why?), but instead, we need to do Fourier series. 
 +
 +We are not going to use all eipxe^{ipx} for all pp, but only those that satisfies eipx=eip(x+L)e^{ipx} = e^{ip(x+L)} have the same periodicity. Which mean pp needs to satisfy 
 +p=(2π/L)n p = (2\pi / L) n for some integer nn
 +
 +So, we define
 + e_n(x) = e^{i(2\pi/L) n x}.
 +We define the Fourer series coefficient as
 +cn=1L0Lf(x)en(x)dx c_n = \frac{1}{L} \int_{0}^L f(x) \overline{e_n(x)} dx
 +
 +Given these coefficient cnc_n, can we recover f(x)f(x)? Yes, under some smoothness condition of f(x)f(x), we have
 +f(x)=nZcnen(x). f(x) = \sum_{n \in \Z} c_n e_n(x).
 +
 +
 +
 +
  
  
  
math121a-f23/october_6_friday.1696565652.txt.gz · Last modified: 2023/10/05 21:14 by pzhou